2021
DOI: 10.21873/invivo.12603
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Membrane Fluidity Modulation: A Feedback Regulated Homeostatic System and Target for Pharmacological Intervention

Abstract: Background/Aim: Alterations of plasma membrane fluidity are characteristic of many diseases but the intentional modulation of membrane fluidity with drugs has been less studied. We examined the therapeutic potential of the membrane fluidizer diethyl azelate (DEA) and related azelates. Materials and Methods: The effects of azelates on plasma membrane fluidity and cell signaling were examined in primary human and murine cells and in vivo. Endpoints were queried using single target and multiplexed immunoassays. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(35 citation statements)
references
References 89 publications
4
31
0
Order By: Relevance
“…We have examined DEA metabolism in hepatocytes from representative animal models in a side-by-side comparison with human hepatocytes. In the past, we have shown that DEA was non-toxic up to concentrations as high as 25% v/v in different types of normal human cells [6]. In the present studies in mammalian hepatocytes, the concentrations of DEA corresponded to the anticipated liver levels of the ester following a single oral or an intravenous dose in vivo.…”
Section: Metabolism and Metabolic Profile Of Dea In Vitro Using Rat Dog Monkey And Human Hepatocytessupporting
confidence: 60%
See 4 more Smart Citations
“…We have examined DEA metabolism in hepatocytes from representative animal models in a side-by-side comparison with human hepatocytes. In the past, we have shown that DEA was non-toxic up to concentrations as high as 25% v/v in different types of normal human cells [6]. In the present studies in mammalian hepatocytes, the concentrations of DEA corresponded to the anticipated liver levels of the ester following a single oral or an intravenous dose in vivo.…”
Section: Metabolism and Metabolic Profile Of Dea In Vitro Using Rat Dog Monkey And Human Hepatocytessupporting
confidence: 60%
“…Building upon our earlier findings that demonstrated lack of DEA mutagenicity using in silico and in vitro assays [6], we have further expanded the study to include a panel of Samonella strains commonly used in testing developmental drugs [32]. The concentrations of DEA spanned a broad range, corresponding to approximately 1000% of the intended oral dose.…”
Section: Toxicity and Mutagenicitymentioning
confidence: 99%
See 3 more Smart Citations